Budaya Organisasi (Organizational Culture), Salah Satu Sumber Keunggulan Bersaing Perusahaan di Tengah Lingkungan yang Selalu Berubah - Son Wandrial (Bina Nusantara University, 2012)
As the world has grown more turbulent, the concept of culture has become increasingly important to organizational leaders because the new environment often calls for new values and fresh approach to doing business. Most leaders now understand that when a company’s culture fits the needs of its external environment and company strategy, employee can create an organization that is tough to beat. The method used in this writing is literature study, through literature materials from several sources. There are a lot of examples in success or failure of a company based on their applied organization culture. Google is one company which success in applying adaptive culture in their organization. This example should be modified by other companies to remain in exchanging world and to reach vision and mission in the future.